Spatio-temporal patterns based on demographic and genetic diversity of the purple sea urchin Paracentrotus lividus in the area around Corsica (Mediterranean Sea) - DUCHAUD, SOPHIE; DURIEUX, ERIC D.H.; COUPE, STEPHANE; PASQUALINI, VANINA; TERNENGO, SONIA (Mediterranean Marine Science, 2018)
Sea urchins were harvested for decades in many areas throughout its distribution range, potentially leading to population collapse. In France, the purple sea urchin Paracentrotus lividus is intensively harvested. Yet, the demography and population dynamics remained under-documented, particularly in Corsica. In this context, we have characterized the fluctuations in density of several size classes at 8 sites around the island, and assessed the genetic diversity and structuring of the population. Densities recorded lie between 0 and 2.18 (± 0.41) individuals.m-2 and spatio-temporal variabilities have also been highlighted. The study of the influence of vegetation cover on the size classes suggests that small- and medium- sized individuals prefer substrates of intermediate heights, whereas individuals with a diameter ≥ 5 cm are more often observed on encrusting substrates, and may be responsible for the continuation of this type of benthic community. The genetic study indicates a high genetic diversity with a low genetic structuring. The Ne values obtained are similar to those described in previous papers. Due to estimates of local contemporary Ne and the homogeneous genetic diversity, our data tend to show that the Corsican population of P. lividus is not overexploited.